Cleaning behavior based on waste textile before resource conversion and its challenges in China – A comprehensive review. (10th October 2022) - Han, Fei; Lang, Chenhong; Qiu, Yiping
Abstract: As the reverse management of the textile industry, the recycling of waste textiles alleviates resource shortage and environmental pressure. The treatments mainly involve exports, second-hand transactions, resource recovery and energy recovery. The safety of the textile recycling industry is facing increasing criticism because of extensive sources and excessive reliance on manual operation. This has led to a desire to move towards harmless recycling of waste textiles, which will implement clean concepts and technologies to protect the health and safety of recyclers, operators and recipients. So far, commercial washing services can support sustainable use of waste textiles. In contrast, the cleaning for recycling as a resource has received little attention. Especially in frequent epidemics, a complete cleaning procedure for waste textiles holds great promise for the safety of the recycling environment. The comprehensive system of decontamination, disinfection and decolorization is defined as a broad sense of cleaning behavior. This paper reviews the application of various physical, chemical and biological technologies in the cleaning process, the influencing factors, technical difficulties and feasibility of each technology. Within the context of cleaner production, green decontamination has become a trend. Multi-disinfection can greatly improve the disinfection, reducing the overuse of disinfectants. Compared with bio-decolorization, ultrasonic technology, photocatalytic technology, electrochemical technology and ozone treatment, which are commonly used in decolorization of textile industry wastewater, show excellent feasibility in that of waste textiles. The review identifies gaps in the availability of combination mode, as without comprehensive data, further decisions cannot be made. The results presented in this paper must be viewed in a broader context of cleaner production: three-in-one is the most ideal production process. However, the results of this study will aid reasonable product framework for life cycle planning making by textile designers and recycling executors, as well as being of use to researchers. Graphical abstract: Image Image. 1 Highlights: The operation mechanism of waste textile cleaning system is proposed. Green washing relies on the optimization of washing conditions and water purification technology. Biotechnology is not suitable for just-in-time industrial production of disinfection and decolorization in waste textiles. The improvement of system efficiency needs combination, and three-phase integration is the ideal mode.